2014
DOI: 10.1111/jgs.12653
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Muscle Quality over the Adult Life Span and Biological Correlates in the Baltimore Longitudinal Study of Aging

Abstract: Background/Objectives Previous studies demonstrated that in older persons decline in muscle strength occurs with aging more rapidly than loss of muscle mass, highlighting the importance of muscle quality for functional outcomes in later life. We examine differences in a proxy measure of muscle quality across the adult life-span and explore potential mechanisms of muscle quality change through identification of cross-sectional correlates of muscle quality. Design Cross-sectional study. Setting/Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
112
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 131 publications
(125 citation statements)
references
References 42 publications
8
112
0
5
Order By: Relevance
“…In addition, any intramuscular fat that was macroscopically detectable was also excluded from the calculation of muscle area. Muscle quality was defined as the ratio of maximum left quadriceps peak torque (N·m) to thigh muscle cross‐sectional area (cm 2 ) (Moore et al ., 2014). …”
Section: Methodsmentioning
confidence: 99%
“…In addition, any intramuscular fat that was macroscopically detectable was also excluded from the calculation of muscle area. Muscle quality was defined as the ratio of maximum left quadriceps peak torque (N·m) to thigh muscle cross‐sectional area (cm 2 ) (Moore et al ., 2014). …”
Section: Methodsmentioning
confidence: 99%
“…In addition to age-related neural impairments affecting locomotion (e.g. Guillet et al 1999; Manini et al 2013), both the velocity and force of muscle contraction appear to decrease to a greater extent than would be predicted based solely on the loss of mass (Brooks et al 1994; Yu et al 2007; Mitchell et al 2012; Miller et al 2013; Moore et al 2014), i.e. the force per cross sectional area is reduced.…”
Section: Introductionmentioning
confidence: 90%
“…The underlying pathophysiological mechanisms for heterogeneous rated of muscle strength decline are still not understood. Recent evidence suggested that the age-related decline in muscle strength is greater than what expected by the decline in muscle mass alone, with consequent decrease of the strength to mass ratio, which has been termed biomechanical muscle quality (7,8). Interestingly, decreased muscle strength is a much better predictor of functional limitation and poor health in older adults that muscle mass alone (9).…”
mentioning
confidence: 99%